Genetic variation of Pyrenophora teres f. teres isolates in Western Australia and emergence of a Cyp51A fungicide resistance mutation - Ellwood, Simon; Piscetek, V.; Mair, W.; Lawrence, J.; Lopez-Ruiz, Fran; Rawlinson, C. (Wiley-Blackwell, 2018)
Plant Pathology published by John Wiley & Sons Ltd on behalf of British Society for Plant Pathology. Genome-wide, unlinked, simple sequence repeat markers were used to examine genetic variation and relationships within Pyrenophora teres f. teres, a common pathogen of barley, in Western Australia. Despite the region's geographic isolation, the isolates showed relatively high allelic variation compared to similar studies, averaging 7.11 alleles per locus. Principal component, Bayesian clustering and distance differentiation parameters provided evidence for both regional genotypic subdivision together with juxtaposing of isolates possessing different genetic backgrounds. Genotyping of fungicide resistant Cyp51A isolates indicated a single mutation event occurred followed by recombination and long-distance regional dispersal over hundreds of kilometres. Selection of recently emergent favourable alleles such as the Cyp51A mutation and a cultivar virulence may provide an explanation, at least in part, for juxtaposed genotypes. Factors affecting genotypic composition and the movement of new genotypes are discussed in the context of grower practices and pathogen epidemiology, together with the implications for resistance breeding.